A national plan of coastal erosion takaful scheme - Nurfarhana Ahmad Saufi
Coastal erosion is a natural disaster and is becoming one of the major concerns among the coastal community in Malaysia. Coastal erosion results in the destruction of the affected areas, including damage to house and property. The coastal erosion phenomenon has become a major challenge for society when adapting and coping with this worsening risk. Appropriate strategies and effective measures should be taken to reduce the risk of coastal erosion. The post-disaster recovery process involves high costs and tends to be a financial burden to the coastal community . Therefore, the main purpose of this study was to identify damage cost incurred when coastal erosion strikes, determine a reasonable contribution payable by the coastal community towards the scheme and propose a National Plan of Coastal Erosion Takaful Scheme for the coastal community in Malaysia. Data for this study were obtained using both quantitative and qualitative approaches. For the quantitative approach, the data were obtained using a questionnaire. A total or 400 respondents from coastal communities from selected states participated in this study. Then, quantitative data was analyzed using SPSS. Qualitative approaches were based on interview methods through focus group discussions involving Bank Negara Malaysia, takaful operators, and academicians. The result of this interview was analyzed manually. The findings how that 48% of coastal communities suffered losses amounting to approximately RM51,000 to RM100,000 due to coastal erosion that damaged their houses. Meanwhile, 40% had suffered property damage costing approximately RM1001 to RM10,000. According to the findings, the coastal community had agreed to participate in the scheme. Moreover, they also agreed to make a contribution based on an affordable amount without any coercion from other parties, such a Takaful operator. Based on the results , most of the coastal community (37.3%) strongly agreed to contribute to an amount ranging from RM50 to RM 100. In term of significant, the study aim to contribute to the existing corpus of knowledge on the development of the coastal erosion Takaful scheme in Malaysia and as a contribution to new knowledge for various stakeholder. The scheme will alleviate the financial burden of the coastal community in case of a coastal erosion disaster. Besides, it become the roles and responsibilities of Takaful Operator, the MNRE, as well as the Bank Negara Malaysia with highlighted in risk reduction. The main implication of this study is that there is a very high willingnes to support the introduction of the scheme to be undertaken by the coastal community as well as individuals who ar willing to pay the premium and are interested in participating in this scheme. The findings showed that this study was able to identify the cost of damage to house and other properties caused by coastal erosion. The cost of damage ha become a gauging indicator or value for Takaful operators when determining a reasonable contribution payable a protection against loss. The coastal community is also aware of the importance of Takaful protection against property due to the increasingly dangerous coastal erosion phenomenon. Subsequently, the scheme can be used to maximize the welfare of coastal communities by minimizing their financial burden caused by coastal erosion problems.